Cultivar innovation: impacts of adoption and potential for adaptation - Ala-Kokko, Kristiina (My University, 2025)
Chapter 1 – From Field Trials to Farm Adoption: Identifying the Productivity Effect of On-Farm Technology Adoption Technology adoption is an important farm management decision and is frequently made using information that is unavailable to the researcher. Aside from their own experiences, producers often rely on extension services to inform their adoption decisions. Here, we propose a novel instrumental variable (IV) approach to identify the effect that a new technology, genetically modified (GM) corn, has on farm yield using instruments constructed from extension information. The proposed approach allows us to explore the degree of the endogeneity bias in estimating the impact of GM adoption on farm productivity. Candidate instruments are constructed from variety trial data to resemble information acquired by producers from university extension variety trial reports and are spatially merged with on-farm production data. We find that failure to account for the endogeneity of the adoption decision does indeed result in a substantial upward bias in the estimated productivity gains. After correcting for this bias through our IV approach, GM corn results in large on-farm yield gains of 19.6 bushels per acre. We demonstrate that variety trial data can be used to estimate the on-farm impact of a new technology, and this approach is general enough to be applied to additional contexts (i.e., technologies, crops, and/or locations). Chapter 2 – Effects of Warming on Cool-Season Pulse Varieties in North America Climate change is expected to have detrimental impacts on agriculture at low latitudes, some of which are already being felt. The impacts at high latitudes are less certain and are still debated. We examine the impacts of warmer temperatures at high latitudes using a novel cool-season pulses field trial dataset that includes 87 locations in the Northern Plains of the United States and western Canada from 2001 to 2023. Using regression analysis, we identify temperature thresholds of 29°C for field peas and 30°C for lentils, beyond which yield reductions begin due to heat stress. A moderate +2°C warming severely reduces field pea and lentil yields by 15.7% and 18.9%, respectively. Projected warming scenarios are extended to estimate the impacts on test weight and protein content, finding that warming has small negative effects on test weight (-0.9% to -0.1%) and moderate positive effects on protein content (+2.5% to +5.6%). Findings suggest that even at high latitudes, breeding programs should prioritize heat resilience to mitigate the detrimental effects on yield of pulse crops under future warming scenarios. Chapter 3 – Heterogeneous Effects of Yield and Quality for Herbicide Tolerant Lentil Varieties Weeds are a significant biotic stressor on crop production globally. In Canada and the United States, traits for herbicide tolerance (HT) developed through genetic engineering (GE) have been limited to crops produced for animal feed, fuel, and fiber, while crops produced for human food consumption have more limited options for weed control. Clearfield varieties are a non-GE alternative that allows producers to selectively target weeds using chemical herbicides. Using variety trial data that includes over 6,600 observations from 2001 to 2023, we quantify the effects of HT technology on lentil outcomes in western Canada and the Northern Plains of the United States. Our main findings reveal the heterogeneous effects of HT on lentil output across two important dimensions, yield and test weight. This distinction is important as HT varieties result in a yield reduction of 4.2% and an increase in test weight by 0.5%. Although there is a yield reduction overall, we find that HT improves yield by 3.4% for each day early season weed interference. Later in the growing season when weed interference impacts lentil quality, HT increases test weight by 0.1% for each additional day of weed interference. Taken together, our results suggest that HT technology in lentils provides risk reducing benefits for production and may be a potential adaptation strategy for producers facing increased weed pressure at higher latitudes due to warmer temperatures.
Keywords: Climate change; Genetically modified crops; Technology adoption; Variety trials